2015
DOI: 10.1371/journal.pmed.1001892
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading a Piped Water Supply from Intermittent to Continuous Delivery and Association with Waterborne Illness: A Matched Cohort Study in Urban India

Abstract: BackgroundIntermittent delivery of piped water can lead to waterborne illness through contamination in the pipelines or during household storage, use of unsafe water sources during intermittencies, and limited water availability for hygiene. We assessed the association between continuous versus intermittent water supply and waterborne diseases, child mortality, and weight for age in Hubli-Dharwad, India.Methods and FindingsWe conducted a matched cohort study with multivariate matching to identify intermittent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 37 publications
3
96
0
2
Order By: Relevance
“…The water policy literature has shown that intermittent water supply imposes significant costs on households, especially with respect to water quality and human health (Kumpel & Nelson, 2013;Ercumen et al, 2015). Unpredictable supplies impose particularly large costs, especially upon household members tasked with managing the water (Pattanayak et al, 2005;Subbaraman et al, 2015;Zérah, 2000).…”
Section: Household Welfare Effectsmentioning
confidence: 99%
“…The water policy literature has shown that intermittent water supply imposes significant costs on households, especially with respect to water quality and human health (Kumpel & Nelson, 2013;Ercumen et al, 2015). Unpredictable supplies impose particularly large costs, especially upon household members tasked with managing the water (Pattanayak et al, 2005;Subbaraman et al, 2015;Zérah, 2000).…”
Section: Household Welfare Effectsmentioning
confidence: 99%
“…The matched cohort design seeks to minimise the risk of unmeasured confounders by matching on characteristics likely to impact outcomes of interest (Austin, 2011;Stuart, 2010). This design has been used in other studies of pre-existing interventions where randomization is not possible (Arnold et al, 2009(Arnold et al, , 2010Ercumen et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…However, service reliability can affect potential health gains from on-plot water access. Households with more reliable water service have been shown to experience less diarrhea (Majuru et al, 2011) and bloody diarrhea (Ercumen et al, 2015) than households with intermittent service.…”
Section: Introductionmentioning
confidence: 99%